Programmed Catalytic Therapy-Mediated ROS Generation and T-Cell Infiltration in Lung Metastasis by a Dual Metal-Organic Framework (MOF) Nanoagent - Bhanu Nirosha Yalamandala; Pin-Hua Chen; Thrinayan Moorthy; Thi My Hue Huynh; Wen-Hsuan Chiang; Shang-Hsiu Hu (MDPI AG, 2022)
Nano-catalytic agents actuating Fenton-like reaction in cancer cells cause intratumoral generation of reactive oxygen species (ROS), allowing the potential for immune therapy of tumor metastasis via the recognition of tumor-associated antigens. However, the self-defense mechanism of cancer cells, known as autophagy, and unsustained ROS generation often restricts efficiency, lowering the immune attack, especially in invading metastatic clusters. Here, a functional core-shell metal-organic framework nanocube (dual MOF) doubling as a catalytic agent and T cell infiltration inducer that programs ROS and inhibits autophagy is reported. The dual MOF integrated a Prussian blue (PB)-coated iron (Fe2+)-containing metal-organic framework (MOF, MIL88) as a programmed peroxide mimic in the cancer cells, facilitating the sustained ROS generation. With the assistance of Chloroquine (CQ), the inhibition of autophagy through lysosomal deacidification breaks off the self-defense mechanism and further improves the cytotoxicity. The purpose of this material design was to inhibit autophagy and ROS efficacy of the tumor, and eventually improve T cell recruitment for immune therapy of lung metastasis. The margination and internalization-mediated cancer cell uptake improve the accumulation of dual MOF of metastatic tumors in vivo. The effective catalytic dual MOF integrated dysfunctional autophagy at the metastasis elicits the ~3-fold recruitment of T lymphocytes. Such synergy of T cell recruitment and ROS generation transported by dual MOF during the metastases successfully suppresses more than 90% of tumor foci in the lung.